Invisible growth of microstructural defects in graphene chemical vapor deposition on copper foil. (January 2016) - Zhang, Yanhui; Zhang, Haoran; Li, Feng; Shu, Haibo; Chen, Zhiying; Sui, Yanping; Zhang, Yaqian; Ge, Xiaoming; Yu, Guanghui; Jin, Zhi; Liu, Xinyu
Abstract: Microstructural defects (MSDs) in graphene are a primary negative factor for the crystal quality and electrical properties of graphene and there is little knowledge about their formation. Here we report the formation mechanism of MSDs in graphene domains during the CVD growth on Cu substrate. Hydrogen-etching results show that an etched graphene hole corresponds to the position of a MSD that appears not only at the nucleation sites of graphene. Based on density-functional calculations, a hidden growth mechanism of MSDs that is driven by defects/impurities (e.g., Cu clusters/particles) on substrate surfaces is proposed. Our model indicates that the number of MSDs in a graphene domain depends on the density of surface defects on the Cu substrate and we demonstrate that MSDs in graphene can be significantly reduced by the careful substrate polishing.